Etude de l’activité biologique des extraits aqueux d’Euphorbia guyoniana (Euphorbiaceae) récoltée dans Oued Sebseb (Sahara Algérien) (El-Wahat Journal for Research and Studies, 2015)
The study focuses on the toxicity of leaf extracts of Euphorbia guyoniana Boiss. & Reut (Euphorbiaceae), harvested in Oued sebseb, northern Sahara eastern Algeria on some bacterial and fungal strains. The crude extract of Euphorbia guyoniana has low antibacterial activity for Staphylococcus aureus with an area of 8.5 mm, and Escherichia coli is 7.67 mm; Protus mirabilis for 7mm; and Micrococci lutus and Bacillus subtilis by 6mm inhibition zone, and therefore also for the other dilutions were labeled low less antimicrobial activity of 8mm, except for Staphylococcus aureus resulting in a 9.33 mm zone of inhibition with the 10-6 and 10-4 with 8.33 dilution. The study of the antimicrobial activity of aqueous extracts of E. guyoniana reveals weak antimicrobial activities. Keywords: Euphorbia guyoniana, aqueous extract, antimicrobial activity, Sahara.